(3GdefJbi ef cJGH GdLgGOs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3CMeO Hf eMeO Hf CMeO GdedbH HQVi s)
(3ChdgG (B:s
(3Yf CHj gQjQI QVi Gddg Yfg bGd (B( (3SCd QLd GdfHi Udi Gddg Ydjg hSde (B: (3Ci GdC(B'(3eGd CaVd bGd GdEjeGf HGddg bGd Ke eGPG bGd GdLgGO ai SHjd Gddg bGd Ke eGPG bGd ML eHQhQ(B) s
(3BNQgG (B:s
(3Yf YeQGf Hf MUjf bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B:- ( (3bjGe QLd ai Ua ai SHjd Gddg YR hLd CaVd ef YHGOJg SJjf SfI bGd haOhI ai SHjd Gddg ChQhMI NjQ ef GdOfjG heG ajgG (B) (3hGdMeO ddg hSdGeg Ydi YHGOg GdPjf EUWai s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3EfJbGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs